2021
DOI: 10.1186/s12872-020-01841-2
|View full text |Cite
|
Sign up to set email alerts
|

ACEF performed better than other risk scores in non-ST-elevation acute coronary syndrome during long term follow-up

Abstract: Background Risk stratification of patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) is an important clinical method, but long-term studies on patients subjected to all-treatment strategies are lacking. Therefore, the aim was to compare several established risk scores in the all-treatment NSTE-ACS cohort during long-term follow-up. Methods Consecutive patients (n = 276) with NSTE-ACS undergoing coronary angiography were recruited bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this respect, we wanted to examine its effect on quantitative data, and to the best of our knowledge, this is the first study in the literature. In a study, it was reported that the ACEF risk score was a better predictor than other risk scores in patients with non-ST-elevation MI in whom all treatment strategies were applied 11 . In another study, it was reported that the ACEF value at admission could predict the 1 month and 1 year cardiac mortality rate after emergency PCI in STEMI patients aged ≥75 years 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, we wanted to examine its effect on quantitative data, and to the best of our knowledge, this is the first study in the literature. In a study, it was reported that the ACEF risk score was a better predictor than other risk scores in patients with non-ST-elevation MI in whom all treatment strategies were applied 11 . In another study, it was reported that the ACEF value at admission could predict the 1 month and 1 year cardiac mortality rate after emergency PCI in STEMI patients aged ≥75 years 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, we wanted to examine its effect on quantitative data, and to the best of our knowledge, this is the first study in the literature. In a study, it was reported that the ACEF risk score was a better predictor than other risk scores in patients with non-ST-elevation MI in whom all treatment strategies were applied 11 . In another study, it was reported that the ACEF value at HDL: High-density lipoprotein; LDL: low-density lipoprotein; MPV: mean platelet volume; TSH: thyroid-stimulating hormone; AST: aspartate aminotransferase; ALT: alanine aminotransferase; Group I: ACEF score≤1.17 (low risk); Group II: ACEF score>1.17 (high risk).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, different models were created for patients with ACS by combining the ACEF score with various clinical and angiographic variables, which enhanced the power of this scoring scheme to predict outcomes [ 28 31 ]. On the other hand, in a recent study by Kristić et al with NSTEMI patients, the ACEF score showed better discrimination than the other six clinical, angiographic, or combined risk scores [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 The ACEF risk score also predicted MACE more effectively over the long-term than other risk scores (GRACE, SYNTAX) in patients with non-ST-elevation myocardial infarction (NSTEMI) who underwent various treatment strategies. 6 The investigators concluded that the ACEF risk score is a quick and simple tool for classifying NSTEMI patients.…”
Section: Introductionmentioning
confidence: 99%